2014
DOI: 10.1590/0074-0276140049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunological changes in Epstein-Barr virus co-infection in Egyptian chronic HCV patients

Abstract: Epstein-Barr virus (EBV) plays a major role in liver pathology. Similar to other members of the herpesvirus family, EBV establishes a persistent infection in more than 90% of adults. The aim of this study was to evaluate the impact of EBV and chronic hepatitis C co-infection (HCV) on biochemical and immunological responses in patients. The study was conducted in 62 patients and 33 apparently healthy controls. Patients were divided into three groups: group I, consisting of 31 patients with chronic hepatitis C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Clinical studies have demonstrated that IL-15 combined with cytokines derived from other monocytes/macrophages can effectively enhance the toxic activity of NK cells, which play an important role in the early defense of the host against viral infection and malignant transformation, suggesting that IL-15 can efficiently enhance the immunity of the host (19,20). It has been noted in studies that IL-15 is closely associated with intracellular infection in human herpesvirus infection, EBV, and cells, suggesting that IL-15 is closely associated with infection in the organism (21,22). In this paper, we found that IL-15 showed an abnormal increase in the serum of patients who developed infections after spinal injury surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that IL-15 combined with cytokines derived from other monocytes/macrophages can effectively enhance the toxic activity of NK cells, which play an important role in the early defense of the host against viral infection and malignant transformation, suggesting that IL-15 can efficiently enhance the immunity of the host (19,20). It has been noted in studies that IL-15 is closely associated with intracellular infection in human herpesvirus infection, EBV, and cells, suggesting that IL-15 is closely associated with infection in the organism (21,22). In this paper, we found that IL-15 showed an abnormal increase in the serum of patients who developed infections after spinal injury surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic studies for the promotion of EBV reactivation and EBV-driven tumorigenesis by coinfections have been explored. When the hospitalized patients were coinfected with EBV and HCV, the immune responses could be dampened ( Shoman et al., 2014 ). The PI3K signaling pathway was first reported to play a role in DENV-2’s reactivation of EBV ( Deng et al., 2021 ).…”
Section: Implication Of Diverse Microbial Interacts With Ebv In Ebv-d...mentioning
confidence: 99%
“…For instance, it is long known that HIV infection caused aberrantly higher EBV loads in peripheral blood of infected individuals, ultimately leading to frequent development of EBV-associated diseases (Dolcetti et al, 1995;Van Baarle et al, 2002;Vaghefi et al, 2006;Stevens et al, 2007;Petrara et al, 2012;Hernandez et al, 2018;Yan et al, 2018). Investigations in South Africa also revealed a direct molecular link between malaria infection and EBV reactivation in circulating mononuclear cells in affected children (Chene et al, 2007;Njie et al, 2009;Reynaldi et al, 2016), and coinfection of EBV and HCV had been reported to dampen immune responses in hospitalized patients (Shoman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%